2004
DOI: 10.1002/jcb.20058
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoptosis and caspase‐3 in vascular smooth muscle cells by plasminogen activator inhibitor type‐1

Abstract: Increased expression of plasminogen activator inhibitor type 1 (PAI-1) is associated with decreased apoptosis of neoplastic cells. We sought to determine whether PAI-1 alters apoptosis in vascular smooth muscle cells (VSMC) and, if so, by what mechanisms. A twofold increase in the expression of PAI-1 was induced in VSMC from transgenic mice with the use of the SM-22alpha gene promoter (SM22-PAI+). Cultured VSMC from SM22-PAI+ mice were more resistant to apoptosis induced by tumor necrosis factor plus phorbol m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 59 publications
1
84
0
2
Order By: Relevance
“…8,20 In the present studies, greater proliferation was demonstrated in VSMCs from PAI-1 transgenic mice (SM22-PAI ϩ ). After 6 days in culture, the average number of SM22-PAI ϩ VSMCs was 2.3Ϯ0.4-fold greater than control VSMCs ( Figure 1A …”
Section: Growth and Proliferation Of Vsmcs From Sm22-pai ؉ Micesupporting
confidence: 53%
See 4 more Smart Citations
“…8,20 In the present studies, greater proliferation was demonstrated in VSMCs from PAI-1 transgenic mice (SM22-PAI ϩ ). After 6 days in culture, the average number of SM22-PAI ϩ VSMCs was 2.3Ϯ0.4-fold greater than control VSMCs ( Figure 1A …”
Section: Growth and Proliferation Of Vsmcs From Sm22-pai ؉ Micesupporting
confidence: 53%
“…Previously we have reported that increased expression of PAI-1 renders VSMCs resistant to apoptosis. 20 The resistance to apoptosis and the induction of increased proliferation appear to be linked. PAI-1 inhibits directly the activity of caspase-3 but not caspase-8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations